2014
DOI: 10.1038/sc.2014.210
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection and bacteriuria in children performing clean intermittent catheterization with reused catheters

Abstract: Study design: This study was designed as a comparative cross-sectional cross-over trial on children performing clean intermittent catheterization (CIC) with reused catheters for 1 or 3 weeks. Objectives: To determine the incidence of symptomatic urinary tract infection (UTI) and bacteriuria (defined as colony count of ⩾ 10 5 colony forming units per ml of a single strain of organism) in these two different frequencies of catheter change. Setting: Multidisciplinary children's neurogenic bladder clinics at two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Retrospective series in paediatric populations show good tolerability of this intervention 29 without increasing the incidence of urinary tract infection. 30 If urethral intermittent catheterisation is problematic, then a continent catheterisable abdominal conduit can be constructed using the Mitrofanoff principle. Patients who have severe incontinence may be managed with a containment strategy using pads (in either sex) or a penile sheath collection system.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective series in paediatric populations show good tolerability of this intervention 29 without increasing the incidence of urinary tract infection. 30 If urethral intermittent catheterisation is problematic, then a continent catheterisable abdominal conduit can be constructed using the Mitrofanoff principle. Patients who have severe incontinence may be managed with a containment strategy using pads (in either sex) or a penile sheath collection system.…”
Section: Discussionmentioning
confidence: 99%
“…No comparison to single-use of catheters was made. 17 A retrospective study by Krassioukov et al 18 (2015) surveyed athletes with spinal cord injuries (n = 61); they found that those who reused the catheters experienced 4±3 UTIs per year while the figures for single-users stood at only 1±1 UTI per year. This association between catheter reuse and UTI was statistically significant (p < .001).…”
Section: Risk Of Utimentioning
confidence: 99%
“…In the school setting, the school nurse may perform or assist a student with clean intermittent catheterization (CIC). Undesirable health consequences, such as urinary tract infection and renal failure, can occur as a result of incomplete emptying of the bladder (Kanaheswari, Kavitha, & Rizal, 2015). The primary purpose of CIC in the school environment is to manage urinary incontinence caused by neurogenic bladder, reduce urinary tract infections, and preserve renal function.…”
Section: Clean Intermittent Catheterizationmentioning
confidence: 99%